Business and conflict in fragile states the case for pragmatic solutions - Ganson, Brian; Wennmann, Achim (Adelphi (Series) (International Institute for Strategic Studies), 2016)
The analysis and conclusions of this Adelphi book will interest policymakers, business leaders and community advocates alike - all those hoping to mitigate today's conflicts while helping to reduce fragility and build a firmer foundation for inclusive development